Creep test of type austenitic 316L stainless steel at high temperature - Mohammad, Khairul Azhar; Zainudin, Edi Syams; Salit, Mohd Sapuan; Zahari, Nur Ismarrubie; Ali, Aidy (2013)
The aim of this study is to investigate the creep test on static loading of stainless steelmaterials. Theestablished creep analytical modeling was used to predict the creep life of stainlesssteel at high temperature. In order to conduct creep testing, the materials were subjected to constantload and high temperature at 565oC in comparisons with different stresses at the similar temperatures.Time dependent deformation of 316L stainless steel at high temperature at differentloading was investigated in this study.The variationof creep strain rates is clearly shown that thesecondary creep obeyed and well agreement with a power law relationship as the constant increasecreep rate till the tertiary stages of specimen test.